Towards a phenomenological critical theory: Hartmut Rosa’s sociology of the relationship to the world - Gros, Alexis Emanuel (2019)
In this paper, I intend to systematically reconstruct the main lines of Hartmut Rosa’s phenomenological approach to Critical Theory. In order to do so, I will proceed in three steps. First (1), as a preliminary, I will briefly present Axel Honneth’s conception of Critical Theory of Society. Second (2), I will sketch out Rosa’s account of the fundamental features of a contemporary version of Critical Theory. Finally (3), I will outline his novel “sociology of the relationship to the world”, especially focusing on the phenomenological opposition between “resonance” and “alienation”.